2020
DOI: 10.1371/journal.pgen.1008625
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous missense variant in CACNB4 encoding the auxiliary calcium channel beta4 subunit causes a severe neurodevelopmental disorder and impairs channel and non-channel functions

Abstract: P/Q-type channels are the principal presynaptic calcium channels in brain functioning in neurotransmitter release. They are composed of the pore-forming Ca V 2.1 α 1 subunit and the auxiliary α2δ-2 and β 4 subunits. β 4 is encoded by CACNB4, and its multiple splice variants serve isoform-specific functions as channel subunits and transcriptional regulators in the nucleus. In two siblings with intellectual disability, psychomotor retardation, blindness, epilepsy, movement disorder and cerebellar atrophy we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 103 publications
1
16
0
Order By: Relevance
“…It has also been suggested that UBTOR/ MINAR1 is implicated in Notch signaling and angiogenesis [13]. The in vivo function of UBTOR is largely unknown, except as a candidate gene in various cancers, and it has also been reported in genetic studies of neurodevelopmental disorders and intellectual disability [33]. Our results in this study showed that disruption of ubtor in zebrafish resulted in motor hyperactivity and elevated neuronal activity.…”
Section: Discussionsupporting
confidence: 60%
“…It has also been suggested that UBTOR/ MINAR1 is implicated in Notch signaling and angiogenesis [13]. The in vivo function of UBTOR is largely unknown, except as a candidate gene in various cancers, and it has also been reported in genetic studies of neurodevelopmental disorders and intellectual disability [33]. Our results in this study showed that disruption of ubtor in zebrafish resulted in motor hyperactivity and elevated neuronal activity.…”
Section: Discussionsupporting
confidence: 60%
“…20,24 Besides, it is involved in the targeting of subunits (like CACNB4) of voltage-gated calcium channels to the nucleus. 25 Multiple essential functions of this protein make it an important target of research.…”
Section: Discussionmentioning
confidence: 99%
“…However, its interaction with auxiliary β4 subunit of P/Q-type presynaptic calcium channel may play a role. 25,26 Nuclear translocation of CACNB4-PP2A-PPP2R5D complex regulates transcription of genes like tyrosine hydroxylase. 26 Variations in CACNB4 have been associated with episodic ataxia and epilepsies like genetic generalized epilepsies, DEE, and others.…”
Section: Discussionmentioning
confidence: 99%
“…EA5 is caused by mutations in the voltage-gated calcium channel encoded by the gene CACNB4 ( 30 , 171 , 172 ). Since there are only a few kindreds described, it is difficult to draw conclusions about the phenotypic spectrum.…”
Section: Phenotypical Overlapmentioning
confidence: 99%
“…It appears that in the heterozygous state mutations in CACNB4 lead to autosomal dominant EA5 and/or predisposition to epilepsy (particularly myoclonic and generalized types), but larger-scale human studies have not conclusively confirmed the latter ( 172 ). In the homozygous state, mutations appear cause a more severe neurodevelopmental disorder ( 171 ).…”
Section: Phenotypical Overlapmentioning
confidence: 99%